Application of Number Theory in the Guess Year of Birth Game - Hermawan, Aldi; Kurniadi, Edi; Sylviani, Sisilia (Lembaga Penelitian dan Pengembangan Matematika dan Statistika Terapan Indonesia, PT Anugrah Teknologi Kecerdasan Buatan PT Anugrah Teknologi Kecerdasan Buatan, 2025)
Number theory is a field of mathematics in which numbers are discussed. There are many developments in this theory. Among them are divisibility, modulo, inverse modulo, congruence and Chinese Remainder Theorem. This research focuses on divisibility and the Chinese Remainder Theorem. What is explained in more detail is a study of several divisibility properties and the application of the Chinese Remainder Theorem to the birth year guessing game. This game is quite popular among middle and high school students. Then, it also explains the technicalities and formulas used in the game to be able to guess the number or year of birth in question. The main finding of these work are prove several divisibility properties and the application of the Chinese Remainder Theorem in the guess year of birth game.